Uma análise das actividades laboratoriais incluídas em manuais escolares de Ciências da Natureza (5º ano) e das concepções dos seus autores - Alcina Figueiroa (Universidade do Minho, 2003)
Several research studies indicate that school textbooks of some subjects andgrade levels include closed laboratory activities whose structure is indisagreement with both the syllabus guidelines and the implications of scienceeducation research. The objectives of this article are: to analyse whether or notlaboratory activities included in natural sciences textbooks are in agreementwith both the theoretical foundations on the use of the laboratory for teachingand with the syllabus recommendations on the same issue; and to analyse theconsistency of the textbooks authorsconceptions with the characteristics ofthe activities they propose in their own textbooks. Twelve textbooks wereanalysed and eleven authors were interviewed. The results of the studyindicate that laboratory activities are very similar in nature and have a low levelof openness. On the other hand, textbook authors see those activities as ameans to illustrate concepts and to develop manipulative competencies. Thus,school textbooks as well as their authorsconceptions seem to be indisagreement with the acknowledged perspectives for the use of thelaboratory activities as well as with the syllabus recommendations.